Co-infection of dengue fever and hepatitis A in a Russian traveler. (2016) - Volchkova, Elena; Umbetova, Karina; Belaia, Olga; Sviridova, Maria; Dmitrieva, Ludmila; Arutyunova, Daria; Chernishov, Dmitriy; Karan, Ludmila
Abstract: We report a hepatitis A (HAV) and dengue virus (DENV) co-infection in Russian man who had been traveling to Dominican Republic. At admission to the hospital hemorrhagic and jaundice symptoms were observed in patient. PCR tests of blood serum and urine revealed RNA dengue virus type 3, HAV RNA, anti-HAV-IgM.